AKUISISI ARSIP SEBAGAI UPAYA PENYELAMATAN BAHAN PERTANGGUNGJAWABAN PEMERINTAH DAERAH (Pada Dinas Perpustakaan dan Kearsipan Kota Bukittinggi) - Tri Purwani; Wendra Yunaldi; Syahril Syahril (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
In accordance with the mandate of Law Number 43 of 2009 concerning Archives that in the context of efforts to save static archives as proof of government accountability, the archive creators should be able to establish good cooperation with Regional Archive Institutions in their respective areas by submitting static archives to the Institution. Regional Archives (Acquisition). However, in reality there are still many creators of archives and archival institutions who do not understand the importance of these acquisitions, so they have not been carried out as they should. The purpose of this study was to determine the extent to which the implementation of static archive acquisition activities at the Bukittinggi City Library and Archives Service as the Regional Archives Institution within the Bukittinggi City Government has the duty and responsibility to carry out static archive acquisition activities, especially within the Bukittinggi City local government environment. , as well as conformity of the procedures for the acquisition of static archives with existing laws and regulations. This study uses an empirical juridical method so that it can be seen the gap between the rules and their implementation in institutions. The results of this study indicate that the procedure for carrying out static archive acquisition activities within the Bukittinggi City government has been carried out in accordance with existing regulations, but is constrained by static archive storage facilities and infrastructure and the limited number of available archivists, so that the expected results of these activities are not in accordance with hope.